Pengaruh Sarana-Prasarana dan Dukungan Peran Keluarga terhadap Keberlangsungan Antenatal Care Terpadu - Madinah Munawaroh; Rizkiana Putri (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
The main approaches to reducing maternal mortality is through the Antenatal Care (ANC) program. ANC is a structured intervention that includes observation, education, and medical procedures designed to ensure a healthy pregnancy and smooth delivery, while reducing the risk of maternal and infant morbidity and mortality. This study aims to determine the impact of the availability of facilities and infrastructure and the role of families on the implementation of Integrated Antenatal Care in 2024. The study employed a descriptive-analytic design with a cross-sectional approach and quantitative methods. A total of 53 respondents were selected as the sample. Data were collected using questionnaires and observation sheets, and analyzed using descriptive statistics and the chi-square test. The results showed that more than half of the respondents (30) did not complete their ANC visits. Meanwhile, 37 respondents considered the available facilities and infrastructure to be adequate, while 31 respondents perceived family support as lacking. Statistical analysis revealed a significant relationship between the availability of facilities and infrastructure and ANC implementation (p = 0.033), as well as between family support and ANC implementation (p = 0.005). In conclusion, adequate facilities and infrastructure, along with supportive family involvement, significantly contribute to the successful implementation of Integrated Antenatal Care in Poskesdes Puser Village, Tirtayasa Subdistrict, in 2024.